2017
DOI: 10.1002/celc.201600921
|View full text |Cite
|
Sign up to set email alerts
|

An Electrochemiluminescent Biosensor Based on Interactions between a Graphene Quantum Dot−Sulfite Co‐reactant System and Hydrogen Peroxide

Abstract: Dedicated to Professor Qinjin Wan on the occasion of his 60th birthdayGraphene quantum dots (GQDs) are recently emerging carbon nanomaterials. GQDs have been recognized as attractive electrochemiluminescence (ECL) luminophores, owing to their environmental friendliness, facile preparation, easy labeling, and high ECL activity. However, in terms of the co-reactant of GQDs ECL, only strongly oxidative S 2 O 8 2À has been well studied and applied in GQD-based ECL sensing, which seriously limits the application of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…In particular, it is essential to monitor the patient's glucose level in a timely manner using a robust portable sensor device. To detect glucose, various techniques have been reported, such as chemiluminescence [14], electrochemiluminescence [15], and electrochemical sensors [16]. Among them, electrochemical sensor devices are currently the A C C E P T E D M A N U S C R I P T best choice.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…In particular, it is essential to monitor the patient's glucose level in a timely manner using a robust portable sensor device. To detect glucose, various techniques have been reported, such as chemiluminescence [14], electrochemiluminescence [15], and electrochemical sensors [16]. Among them, electrochemical sensor devices are currently the A C C E P T E D M A N U S C R I P T best choice.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to explore other, newer co‐reactants of CQDs in order to further reveal the ECL mechanism of CQDs and expand its application. In recent years, it has been found that sulfite (SO 3 2− ), hydrogen peroxide (H 2 O 2 ) and L‐cysteine can be used as co‐reactants of CQDs to enhance the ECL cathode emission [61–63]. In addition, Long et al.…”
Section: Ecl Mechanism Of the Carbon‐based Quantum Dotsmentioning
confidence: 99%
“…In addition, the structure and performance of GQDs can be easily adjusted by changing the precursor, dopant, or modifier in the “bottom-up” method. However, the current method to produce GQDs with the ECL property mainly uses the “top-down” strategy ( Zhang et al, 2015 ; Chen et al, 2016 ; Zhou et al, 2017 ; Jie et al, 2019 ). These methods usually require complex and harsh synthesis procedures.…”
Section: Introductionmentioning
confidence: 99%